Pemberdayaan Masyarakat dan UMKM Melalui Pendampingan Pembuatan Nomor Induk Berusaha (NIB) di Desa Sukamulya - Ani Rosidah; Septian Triana; Siti Nuryanti Dewi Patimah; Riharti Roro Novariyanti; Fajar Reksa (Universitas Pahlawan Tuanku Tambusai, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an essential role in supporting local economic growth. However, many MSME actors still lack business legality in the form of a Business Identification Number (NIB) due to limited information and understanding of the Online Single Submission (OSS) registration process. This community service activity aimed to improve MSME understanding regarding the importance of business legality and provide assistance in obtaining NIBs. The program was conducted in Sukamulya Village, Kertajati District, Majalengka Regency through observation, socialization, mentoring, and evaluation methods. The target participants were MSME owners who had not yet obtained business legality. The results indicated an increase in participants' understanding of the benefits of NIB as a legal business identity, which facilitates access to government programs, business financing, and business development opportunities. Direct mentoring assisted participants in understanding the registration procedures and completing the required documents. This program demonstrates that collaboration among universities, village governments, and communities can strengthen MSME capacity through improved business legality.